2006
DOI: 10.1177/0040517506061964
|View full text |Cite
|
Sign up to set email alerts
|

The Hairiness of Worsted Wool and Cashmere Yarns and the Impact of Fiber Curvature on Hairiness

Abstract: In this study, a range of carefully selected wool and cashmere yarns as well as their blends were used to examine the effects of fibre curvature and blend ratio on yarn hairiness. The results indicate that yarns spun from wool fibres with a higher curvature have lower yarn hairiness than yarns spun from similar wool of a lower curvature. For blend yarns made from wool and cashmere of similar diameter, yarn hairiness increases with the increase in the cashmere content in the yarn. This is likely due to the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Yarns were tested for 13 attributes as described in previous studies (McGregor, 2001;McGregor & Postle, 2007;Wang, Chang, & McGregor, 2006). In brief: linear density (tex); yarn evenness (CVm); yarn thick places (+50%); yarn thin places (À50%); neps (+200%); yarn hairiness (Uster Tester 3 v2.50); yarn elongation (%); yarn tenacity (cN/tex); total number of hairs protruding more than 1 mm (T p , hairs/100 m); number of hairs exceeding 3 mm (S 3, hairs/100 m); S 3 as a percentage of T p (100S 3 /T p ,%); total length of hairs (K', mm/cm); yarn friction (coefficient).…”
Section: Fibre Yarn and Fabric Evaluationmentioning
confidence: 99%
“…Yarns were tested for 13 attributes as described in previous studies (McGregor, 2001;McGregor & Postle, 2007;Wang, Chang, & McGregor, 2006). In brief: linear density (tex); yarn evenness (CVm); yarn thick places (+50%); yarn thin places (À50%); neps (+200%); yarn hairiness (Uster Tester 3 v2.50); yarn elongation (%); yarn tenacity (cN/tex); total number of hairs protruding more than 1 mm (T p , hairs/100 m); number of hairs exceeding 3 mm (S 3, hairs/100 m); S 3 as a percentage of T p (100S 3 /T p ,%); total length of hairs (K', mm/cm); yarn friction (coefficient).…”
Section: Fibre Yarn and Fabric Evaluationmentioning
confidence: 99%
“…44 The yarns made from the lower curvature wools exhibited greater hairiness (6.1 versus 5.8 Uster units), a finding reported previously for lower curvature wool yarns. 45 The fabrics were knitted with no noticeable difference in the knitting performance as commented upon by the knitter. This comment is reasonable given the similar characteristics measured on the yarns.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to compression was measured (AS 3535, 1988 Rovings were tested on the Uster Tester 1-B v5.08 at a test speed of 50 m/min for 2.5 min to determine CVm. Yarns were tested for 13 attributes as described in previous studies (McGregor & Postle, 2007;Wang, Chang, & McGregor, 2006). In brief: linear density (tex); yarn evenness (CVm); yarn thick places (+50%); yarn thin places (−50%); neps (+200%); yarn hairiness (Uster Tester 3 v2.50); yarn elongation (%); yarn tenacity (cN/tex); total number of hairs protruding more than 1 mm (T p , hairs/100 m; the Zweigle G565 Hairiness Meter); number of hairs exceeding 3 mm (S 3, hairs/ 100 m); S 3 as a percentage of T p (100S 3 /T p , %); total length of hairs (K′, mm/cm); yarn friction (coefficient).…”
Section: Spinning Knitting and Finishingmentioning
confidence: 99%
“…It is surprising that there were no effects on fabric clean/hairy handle as the yarns composed of lower curvature superfine wool have been shown to have higher hairiness attributes compared with yarn of the higher curvature wool (McGregor & Postle, 2007;Wang et al, 2006) and that these differences in yarn hairiness have been shown to be associated with other fabric properties (McGregor & Postle, 2007) and wearer assessments of fabrics composed of these yarns (McGregor, Doughty, et al, 2015). Previous research has shown a negative linear response to fabric density, where increasing fabric density was associated with reduced hairiness , and this result was also found in the present work at TF's 15.5 and 17.0 (Table 5).…”
Section: Fibre Curvature Affected Fabric Handle Propertiesmentioning
confidence: 99%